Giant Squamous Cell Papilloma of the Eyelid—Diagnostic and Therapeutic Challenges - Attila Vass; Gábor Vass; Erika Gabriella Kis; Levente Kuthi; Judit Oláh; Tibor Hortobágyi; Edit Tóth-Molnár (Case Reports in Ophthalmological Medicine)
Squamous cell papilloma (SCP) is generally a human papillomavirus (HPV) induced exophytic or endophytic proliferation on the surface of the skin, oral cavity, larynx, esophagus, cervix, vagina, and anal canal. The endophytic type SCP can cause differential diagnostic difficulties with keratoacanthoma, inverted follicular keratosis, and squamous cell carcinoma; however, these lesions are not associated with HPV infection. The authors present a female patient who noticed an extremely rapidly growing tumor destructing the left lower eyelid. The histological analysis of the biopsy sample revealed a virus-induced squamoproliferative lesion. The eyelid affected was completely removed, and the histological examination resulted in a HPV induced endophytic squamous cell papilloma. The tarsus and the conjunctiva were replaced by a chondromucosal graft harvested from the nasal septum, while the skin defect could be closed directly. Restoration of the eyelid function has been achieved with satisfying functional and cosmetic results.